Purification of amorphous boron powder by using the soluble transformation of acid-insoluble boron magnesium compounds (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
At present, amorphous boron powder is considered to be the best fuel for solid fuel-rich propellants due to its extremely high volume calorific value and mass calorific value. Amorphous boron powder produced by magnesium thermal reduction contains many impurities that are insoluble in acids. In addition to impurities, oversized particles, and limited chemical reactivity, these issues significantly restrict the extensive use of this material in military and aerospace sectors. In this paper, the soluble transformation mechanism of insoluble boron magnesium compounds in amorphous boron powder at calcining and a method to purify boron powder were studied. To remove insoluble boron magnesium compounds in amorphous boron powder, insoluble impurities Mg2B2O5 and MgB4 were directionally transformed into soluble MgB4O7 and MgO at calcining. The samples were subsequently subjected to water or acid leaching to convert the crude amorphous boron powder product to high purity. SEM-EDS, XRD, XPS, and other techniques were used to determine the occurrence states of impurity phases. The transformation of impurity phases after calcining water leaching and acid leaching was monitored. The results showed that the magnesium content in the amorphous boron powder was reduced to 0.96%, and the purity of boron powder was increased to 97.34%.
Keywords: amorphous boron powder; purification; magnesium removal; boron magnesium compounds; soluble transformation